Distress And Protest Against Child Bride: Nujood Ali's And Delphine Minoui's I Am Nujood, Age 10 And Divorced (2010) - Fitriani, Norminingsih; , Prof. Dr. C. Bakdi Sumanto; , Dr. Phil. Dewi Candraningrum, M.Ed (2014)
I Am Nujood, Age 10 and Divorced is a memoir which tells the struggle of a woman who fight for woman and child rights. They are learning how to get their needs and gave inspiration to many people generally and to Yemeni especially. Nujood is seen as a little girl around poor and illiteracy ecosystem class who looks full of spirit, courageous and she becomes the hero. Her family is against her, but many people support her. Based on the reason, the author chooses the title Distress and Protest Against Child Bride: Nujood Ali's and Delphine Minoui's I Am Nujood, age 10 and Divorced (2010). The researcher tries to analyze one of the Yemeni culture especially Child marriage in Nujood Ali's and Delphine Minoui's I Am Nujood, Age 10 and Divorced. The researcher wants to know more about the story that appears Nujood's life. Based on the background of the study, the statements of the problems can be formulated as follows: 1) How is the social and historical background of the Yemeni Society in the Latest Twenty Century and Early of Twenty-First Century?, 2) How are the women condition mirrored at Nujood Ali's and Delphine Minoui's I Am Nujood, Age 10 and Divorced (2010)?, 3) How is distress reflected in Nujood Ali's and Delphine Minoui's I Am Nujood, Age 10 and Divorced (2010)? And How is protest against child bride reflected in Nujood Ali's and Delphine Minoui's I Am Nujood, Age 10 and Divorced (2010)?. Theoretical approach being used is by using sociological and feminist frameworks. First, investigates the memoir using sociological analysis to investigate the women condition mirrored by Nujood in the story. Therefore, the study will explore the social and historical background of the Yemeni Society by using C. Kluckhohn theory to understand Culture in Yemen. The next is formulate concept of patriarchy which caused oppression by using the Second Sex point of view and it's also to explore the protest against of child bride. Results of the study show the following conclusions: first, The Constitution of Yemen states that Islam is the official state religion of the country, but it also guarantees freedom of religion but the fact condition in rural area is the depression because of tribal custom, that is early marriage especially for child bride and the revenge idea by the major female character participation in the society to understanding the human right especially for woman right, role and childcare. Second, the researcher suggests that any future researcher to understand that the destiny as a woman becomes a wife and who serves her husband and becomes a mother who gave birth to and take care of the children and keep the family name or family honor. These all is undertaken without any oppression or force.